2004
DOI: 10.1002/jnr.20096
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal NOS activation during oxygen and glucose deprivation triggers cerebellar granule cell death in the later reoxygenation phase

Abstract: The present study investigated the temporal relationship between neuronal nitric oxide synthase (nNOS) activity and expression and the development of neuronal damage occurring during anoxia and anoxia followed by reoxygenation. For this purpose, cerebellar granule cells were exposed to 2 hr of oxygen and glucose deprivation (OGD) and 24 hr of reoxygenation. To clarify the consequences of nNOS activity inhibition on neuronal survival, cerebellar granule cells were exposed to OGD, both in the absence of extracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…Our findings and interpretations are consistent with restricted opening of hemichannels in normal cells adequate to allow release of signaling molecules and with greater opening that may accelerate death under pathological conditions such as ischemia, in which there is enhanced NO generation (25,26). Mutations of the cysteine residues should give a clearer view of hemichannels as a sensor of redox potential and possible target for therapeutic intervention.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our findings and interpretations are consistent with restricted opening of hemichannels in normal cells adequate to allow release of signaling molecules and with greater opening that may accelerate death under pathological conditions such as ischemia, in which there is enhanced NO generation (25,26). Mutations of the cysteine residues should give a clearer view of hemichannels as a sensor of redox potential and possible target for therapeutic intervention.…”
Section: Discussionsupporting
confidence: 83%
“…Because the generation of NO, a free radical, is increased in astrocytes during MI (25,26), and NO can oxidize cysteine residues (24, 27, 28), we tested whether NO donors induce dye uptake by astrocytes. Application of 100 M nitrosoglutathione (GSNO) (Fig.…”
Section: Intracellular But Not Extracellular Gsh Blocks the Dye Uptakmentioning
confidence: 99%
“…The means ± SD from six independent experiments (n = 6). * Differences statistically significant vs. control (one-way ANOVA followed by Dunnett's test, p < 0.05) [28,31,32]. Our previous research has confirmed that the CGC model is suitable for mechanistic studies on toxicity for neurons caused by excitotoxic challenges, calcium imbalance and mitochondrial dysfunction [40,42,43].…”
mentioning
confidence: 54%
“…# Differences statistically significant vs. 5 µM TBBPA (one-way ANOVA followed by Dunnett's test, p < 0.05) When examining the putative mechanism of TBBPA and OGD synergy we considered calcium imbalance, mitochondrial disfunction and oxidative stress. According to literature data, these processes might be common to both of toxic factors studied here [9,14,22,23,25,27,28,32]. Therefore, using standard methods we measured…”
Section: Ros Mediate Tbbpa and Ogd Synergy In Cgc Culturesmentioning
confidence: 96%
See 1 more Smart Citation